2008
DOI: 10.21273/jashs.133.6.810
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Analysis and Single-nucleotide Polymorphism Marker Development in Cultivated Bulb Onion Based on Expressed Sequence Tag–Simple Sequence Repeat Markers

Abstract: Bulb onion (Allium cepa L.) is a globally significant crop, but the structure of genetic variation within and among populations is poorly understood. We broadly surveyed genetic variation in a cultivated onion germplasm using simple sequence repeat (SSR) markers and sequenced regions flanking expressed sequence tag (EST)-SSRs to develop single-nucleotide polymorphism (SNP) markers. Samples from 89 inbred and open-pollinated (OP) bulb onion populations of wide geographical ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 39 publications
(40 reference statements)
5
47
2
Order By: Relevance
“…In contrast, Araki et al (2010) reported their amplification but it was in bulb onion and closely related species of section Cepa and Phyllodon only. EST-SSR primer set revealed an average of 3.2 amplicons (range, 1-7 alleles) and is equal to the average (3.6) reported by McCallum et al (2008). Two primer sets (ACM300, ACM318) and all the three genomic SSRs were monomorphic in onion accessions but they revealed polymorphism between Fig.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…In contrast, Araki et al (2010) reported their amplification but it was in bulb onion and closely related species of section Cepa and Phyllodon only. EST-SSR primer set revealed an average of 3.2 amplicons (range, 1-7 alleles) and is equal to the average (3.6) reported by McCallum et al (2008). Two primer sets (ACM300, ACM318) and all the three genomic SSRs were monomorphic in onion accessions but they revealed polymorphism between Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Currah (2002) explained that short day onions may show greater genetic diversity because they have been maintained as landraces and open pollinated cultivars over a wide geographic area, whereas intermediate and long day cultivars are more localized. Fischer and Bachmann (2000) also revealed groupings based on geographical origins whereas McCallum et al (2008) also observed a clear resolution of a group of Indian cultivars and landraces from the main grouping of short day populations and were of the view that Indian region may have potential to provide novel germplasm resources. The present investigations support this hypothesis and this fact may be further strengthened in future by diversity assessment of short day germplasm from diverse origins.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations